MO201: Effects of Aspirin in Primary Prevention of Cardiovascular (CV) Disease in People with Chronic Kidney Disease (CKD): Results of the TIPS3 Trial. (3rd May 2022) - Mann, Johannes F E; Joseph, Philip; Gao, Peggy; Pais, Prem; Xavier, Denis; Dans, Tony; Lopez Jaramillo, Patricio; Gamra, Habib; Tyrwhitt, Jessica; Yusuf, Salim
Abstract: BACKGROUND AND AIMS: Subjects with CKD carry a high (CV) risk. Whether this risk is blunted by aspirin is controversial. We examined CV outcomes of CKD participants of the TIPS3 trial. METHOD: The International Polycap Study3 (TIPS3) randomized people (N = 5713) with and without CKD, but without previous CV disease, to aspirin, aspirin plus polypill, polypill or respective placebo in a factorial design. In 983 participants that were randomized to aspirin or placebo, eGFR was below 60 mL/min/1.73 m 2 at baseline (CKD). The primary outcome for this comparison was non-fatal myocardial infarction (MI), non-fatal stroke or CV death. The mean follow-up was 4.6 years. RESULTS: In all participants, there were 250 primary MACE outcomes, 116 on aspirin and 134 on placebo (HR 0.86; 95% CI 0.67–1.10). In those with CKD, there were 65 primary MACE outcomes, 26 in the 502 participants on aspirin, 39 in the 481 participants on placebo, HR 0.57 (95% CI 0.34–0.94). Directionally similar results were found for aspirin versus placebo for the secondary outcome all-cause death with 312 events in all participants (HR 0.87; 0.70–1.07) and 82 events in CKD patients (HR 0.64; 0.41–0.99). There was no significant interaction of eGFR <60 mL/min with the treatment effects of aspirin versus placebo. Major and minor bleedings were rare and not different between groups. When aspirin was combined with a polypill (containing atenolol, ramipril, hydrochlorothiazide and simvastatin) and compared to double placebo, in all participants the HR for the MACE outcome was 0.69, 0.50–0.97 and for all-cause death 0.80, 0.59–1.08; in CKD patients the HR was 0.37, 0.18–0.75 for MACE and HR 0.49, 0.29–0.97 for death. CONCLUSION: Results suggest that the CV risk in people with CKD may be substantially alleviated with aspirin alone and in combination with a polypill.